Handedness and Relative Age in International Elite Interactive Individual Sports Revisited - Loffing, Florian; Schorer, Jörg (Frontiers in Sports and Active Living, 2021)
Relative Age Effects (RAE) describe the unintended side-effect of annual age-grouping such that athletes born close to a specific cut-off date are more likely to be associated with attaining higher performance status than athletes born later. One factor suggested to override the RAE is handedness. Given the left-handers’ rarity and their proposed performance advantage in interactive sports, left-handedness may be associated with lower likelihood of suffering from selection inequalities like RAE in those sports compared to right-handedness. Here, in a two-study approach we tested that hypothesis by examining male and female athletes from various interactive individual sports sampled over a 10-year period from 2007 to 2016. Study 1 investigated distributions of birth and handedness of senior athletes listed in the top 200 of year-end world rankings in table tennis, tennis, squash and fencing (épée, foil and sabre). Study 2 followed a similar design, but focused on junior athletes in the fencing disciplines and tennis. Unlike the above prediction, in both studies birth distribution was not found to be reliably associated with handedness in any of the sports or disciplines considered. Left-handers were consistently overrepresented in épée, foil and table tennis, occasionally in sabre and tennis and not at all in squash. Birth frequencies decreased from quartile Q1 (January to March) to Q4 in almost any sporting domain at the junior level, whereas such trend was rarely found at the senior level. In conclusion, while providing novel insight on the role handedness may play at the junior level, our findings do not support the hypothesis that left-handedness helps override birth-related inequalities in high sporting achievement in elite interactive individual sports.